NUMEROS CROMOSOMICOS DE PTERIDOFITOS CHILENOS: PRIMERA CONTRIBUCION - Jara-Seguel, Pedro; Romero-Mieres, Mario; Palma-Rojas, Claudio (Gayana Botánica, 2006)
Mitotic chromosome counts in Chilean pteridophytes confirm the diploidy described for Equisetum L. (2n = 216) and Blechnum L. (2n = 66), as well as the tetraploidy of Asplenium L. (2n = 144). Megalastrum spectabile (Kaulf.) A.R.Sm. et R.C.Moran is diploid (2n = 82), while in metaphases of Polystichum subintegerrimum (Hook. et Arn.) R.A.Rodr. chromosome numbers from ca. 311 to 328 were counted. Tetraploidy was also described in Adiantum chilense Kaulf. (2n = 116).